List of new names and new combinations previously effectively, but not validly, published (International Journal of Systematic and Evolutionary Microbiology, 2011)
The purpose of this announcement is to effect the valid publication of the following effectively published new names and new combinations under the procedure described in the Bacteriological Code (1990 Revision). Authors and other individuals wishing to have new names and/or combinations included in future lists should send three copies of the pertinent reprint or photocopies thereof, or an electronic copy of the published paper, to the IJSEM Editorial Office for confirmation that all of the other requirements for valid publication have been met. It is also a requirement of IJSEM and the ICSP that authors of new species, new subspecies and new combinations provide evidence that types are deposited in two recognized culture collections in two different countries. It should be noted that the date of valid publication of these new names and combinations is the date of publication of this list, not the date of the original publication of the names and combinations. The authors of the new names and combinations are as given below, and these authors' names will be included in the author index of the present issue. Inclusion of a name on these lists validates the publication of the name and thereby makes it available in bacteriological nomenclature. The inclusion of a name on this list is not to be construed as taxonomic acceptance of the taxon to which the name is applied. Indeed, some of these names may, in time, be shown to be synonyms, or the organisms may be transferred to another genus, thus necessitating the creation of a new combination.